SOP Conservative (Medical and Mechanical) Treatment of Erectile Dysfunction. (23rd January 2013) - Porst, Hartmut; Burnett, Arthur; Brock, Gerald; Ghanem, Hussein; Giuliano, Francois; Glina, Sidney; Hellstrom, Wayne; Martin‐Morales, Antonio; Salonia, Andrea; Sharlip, Ira
ABSTRACT Introduction. Erectile dysfunction (ED) is the most frequently treated male sexual dysfunction worldwide. ED is a chronic condition that exerts a negative impact on male self‐esteem and nearly all life domains including interpersonal, family, and business relationships. Aim. The aim of this study is to provide an updated overview on currently used and available conservative treatment options for ED with a special focus on their efficacy, tolerability, safety, merits, and limitations including the role of combination therapies for monotherapy failures. Methods. The methods used were PubMed and MEDLINE searches using the following keywords: ED, phosphodiesterase type 5 (PDE5) inhibitors, oral drug therapy, intracavernosal injection therapy, transurethral therapy, topical therapy, and vacuum‐erection therapy/constriction devices. Additionally, expert opinions by the authors of this article are included. Results. Level 1 evidence exists that changes in sedentary lifestyle with weight loss and optimal treatment of concomitant diseases/risk factors (e.g., diabetes, hypertension, and dyslipidemia) can either improve ED or add to the efficacy of ED‐specific therapies, e.g., PDE5 inhibitors. Level 1 evidence also exists that treatment of hypogonadism with total testosterone < 300 ng/dL (10.4 nmol/L) can either improve ED or add to the efficacy of PDE5 inhibitors. There is level 1 evidence regarding the efficacy and safety of the following monotherapies in a spectrum‐wide range of ED populations: PDE5 inhibitors, intracavernosal injection therapy with prostaglandin E1 (PGE1, synonymous alprostadil) or vasoactive intestinal peptide (VIP)/phentolamine, and transurethral PGE1 therapy. There is level 2 evidence regarding the efficacy and safety of the following ED treatments: vacuum‐erection therapy in a wide range of ED populations, oral L‐arginine (3–5 g), topical PGE1 in special ED populations, intracavernosal injection therapy with papaverine/phentolamine (bimix), or papaverine/phentolamine/PGE1 (trimix) combination mixtures. There is level 3 evidence regarding the efficacy and safety of oral yohimbine in nonorganic ED. There is level 3 evidence that combination therapies of PDE5 inhibitors + either transurethral or intracavernosal injection therapy generate better efficacy rates than either monotherapy alone. There is level 4 evidence showing enhanced efficacy with the combination of vacuum‐erection therapy + either PDE5 inhibitor or transurethral PGE1 or intracavernosal injection therapy. There is level 5 evidence (expert opinion) that combination therapy of PDE5 inhibitors + L‐arginine or daily dosing of tadalafil + short‐acting PDE5 inhibitors pro re nata may rescue PDE5 inhibitor monotherapy failures. There is level 5 evidence (expert opinion) that adding either PDE5 inhibitors or transurethral PGE1 may improve outcome of penile prosthetic surgery regarding soft (cold) glans syndrome. There is level 5 evidence (expert opinion) that the combination of PDE5 inhibitors and dapoxetine is effective and safe in patients suffering from both ED and premature ejaculation. Porst H, Burnett A, Brock G, Ghanem H, Giuliano F, Glina S, Hellstrom W, Martin‐Morales A, Salonia A, Sharlip I, and the ISSM Standards Committee for Sexual Medicine. SOP conservative (medical and mechanical) treatment of erectile dysfunction. J Sex Med 2013;10:130–171.